LINGUISTIC ANALYSIS OF MEDICINAL PLANT NAMES FORMED ON THE BASIS OF FRAME IN ENGLISH (World Bulletin of Social Sciences, 2025)
This article analyzes the features of the formation of names of medicinal plants in English based on frame semantics. The study is based on the frame theory developed by K. Fillmore, which highlights the semantic and conceptual structures of the names of medicinal plants, their cultural and cognitive aspects. The article examines the lexical unit and metaphorical expression of plant terms actively used in the fields of medicine, folk medicine, and pharmacology.